Football : a history of the gridiron game - Stewart, Mark, 1960 July 7- (New York : Franklin Watts, 1998)
Discusses the origins and evolution of the game of football, as well as memorable events and key personalities in the game's history.
Includes appendix.
Recreational and Performing Arts
Keywords: Football -- United States -- History -- Juvenile literature; Football -- History